Pengaruh Word Of Mouth, Fasilitas, dan Motivasi terhadap Keputusan Menjadi Siswa SMA (Studi Kasus pada SMK Markatin Jakarta) - Irfan Arif Husen; Arya Darmawan; Zulkarnaini; Sri Handoko Sakti; Farmansyah Maliki (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
This study aims to determine the influence of word of mouth, facilities, and motivation on the decision to enroll at SMK Markatin Jakarta. The population of this study was all students at SMK Markatin Jakarta. The study sample used a saturated sample of 97 respondents. The research strategy used was a causal associative strategy. Data analysis employed partial coefficient of determination analysis, simultaneous analysis, and hypothesis testing. The data used were primary data. Data collection techniques used questionnaires and documentation. The results of the study indicate that (1) word of mouth significantly influences the decision to enroll at SMK Markatin Jakarta; (2) facilities significantly influence the decision to enroll at SMK Markatin Jakarta; (3) motivation significantly influences the decision to enroll at SMK Markatin Jakarta; and (4) word of mouth, facilities, and motivation simultaneously significantly influence the decision to enroll at SMK Markatin Jakarta.